STRATEGI PENINGKATAN MUTU SEKOLAH BERBASIS ANALISIS SWOT DI SD NEGERI 03 WANAMULYA - Andi Dwi Arifin; Siti Solekha; Tika Ardiani; Ngurah Ayu Nyoman Murniati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the strategy for improving school quality at SD Negeri 03 Wanamulya using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. This approach is used to identify internal and external potentials that affect the quality of education. The study was conducted using a descriptive qualitative method, with data collection through observation, interviews, and documentation studies. The results of the analysis indicate that the main strengths of the school include competent teacher resources, adequate educational facilities, and good relations with the community. Identified weaknesses include the lack of ongoing training programs for teachers and limited operational budgets. The main opportunities include support from the government through education quality improvement programs and community enthusiasm in supporting school activities. However, threats faced include competition with other schools and changes in education policies that are less supportive. Recommended strategies include optimizing the use of internal resources to strengthen learning programs, increasing cooperation with external parties such as other educational institutions and local governments, and managing risks related to threats by preparing flexible strategic planning. The implementation of this strategy is expected to improve the quality of education at SD Negeri 03 Wanamulya in a sustainable manner.